2021
DOI: 10.17159/sajs.2021/8848
|View full text |Cite
|
Sign up to set email alerts
|

Food security and related health risk among adults in the Limpopo Province of South Africa

Abstract: Food insecurity, obesity and hypertension remain major public health issues related to nutrition in South Africa. The purpose of this study was to determine household food security and the health risk of the adult population in the Limpopo Province using cross-sectional designs. A stratified random sampling method was used to recruit adults aged 18 to 65 years in the Limpopo Province of South Africa. Data were collected using a validated, structured questionnaire. All data were analysed using SPSS version 25.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…This is due to many determinant factors that influence food access and consumption. These results align with several studies [2,18,26] conducted in Limpopo regarding the food security status of households; these studies revealed that most households were food insecure. Although Limpopo is known to be a food-secure province in South Africa [3], many rural households still suffer from food insecurity.…”
Section: Discussionsupporting
confidence: 91%
“…This is due to many determinant factors that influence food access and consumption. These results align with several studies [2,18,26] conducted in Limpopo regarding the food security status of households; these studies revealed that most households were food insecure. Although Limpopo is known to be a food-secure province in South Africa [3], many rural households still suffer from food insecurity.…”
Section: Discussionsupporting
confidence: 91%